A Review on Antibiotic Resistance in Bacteria - Jahan, Nazneen (International Journal of Engineering & Technology, 2018)
Antibiotics are now widely used in the treatment of infectious diseases. But the problem arise when the infectious agent become resistant to antibiotic drug therapy. Nowadays misuse of antibiotics in human, agriculture and veterinary medicine is the major reason for increased resistance. Resistance to antimicrobial agentâ€™s results in treatment failure,increased mortality and morbidity. Antimicrobial resistance is now a global problem because resistance can transfer through mobile genetic elements such as plasmids, transposons and integrons. Pathogenic species including staphylococci, Streptococcus pneumonia and Mycobacterium tuberculosis together with commensal enteric bacteria predispose the dual risk of emerging antibiotic resistance. Finally, control of antibiotic resistance bacteria depends on reduction of selection pressure and improved surveillance to detect their subsequent spread.Â Â Â